How is the Internet Changing Labor Market Arrangements? : Evidence from Telecommunications Reforms in Europe - Vazquez, Emmanuel; Winkler, Hernan (World Bank, Washington, DC, 2017)
This paper exploits variations in the timing of telecommunications reforms across Europe to analyze the relationship between the rise of alternative work arrangements and the emergence of the Internet. The paper evaluates whether sectors that are technologically more dependent on information and communications technologies experienced disproportionately larger changes in their employment outcomes after telecommunications reforms were introduced. The main results point to a disproportionate increase in total employment, part-time work, and home-based work among information and communications technologies–intensive sectors after the implementation of telecommunications reforms. The analysis does not find a link between the incidence of temporary employment, self-employment, second job holding, and telecommunications reforms. The main results are robust to several specifications.